EFFECTS OF WEIGHT TRAINING ON PHYSICAL FITNESS AND BODY COMPOSITION ON A WARSHIP - Antonios Vantarakis; Gerasimos Grivas; Stamatios Kalligeros; Konstantinos Karakatsanis; Nikolas Theodorou; Nikolaos Vezos; Anthia-Dimitra Vantaraki; Sotirios A. Vantarakis (Scientific Publishing House. NSA Press, 2023)
Introduction. The military readiness of the naval personnel serving on a warship requires a high level of physical health and fitness which is considered a given capability, regardless of the service they serve. The purpose of this study was to investigate the effects of a weight training program (WTP) on the physical fitness of Greek naval cadets during a training trip on a warship. Material & Methods. The sample consisted of 21 male Greek cadets of the Hellenic Naval Academy (HNA) (age: 21.0 ± 0.83 years, height: 177.9 ± 6.9cm, body mass: 78.2 ± 7.1kg). The cadet team that participated for four weeks on the trip performed 20 training sessions lasting 60-80 min each, five times a week. The measurements of the participants before and after 4 weeks of a weight exercise training program were related to body mass (BM), body fat percentage (% BF), body mass index (BMI), number of sit-ups (SU1) and push-ups (PU1) done in one minute, one repetition maximum (1RM) in a squat (SQ) and bench press (BP), and the 30m run and 5m rope climb. Results. The results of the study showed that the WTP did not affect BM (t20 = -0.412, p = .685 > .05) and BMI (t20 = -0.477, p = .639>.05). Respectively, no significant difference was observed in %BF in all cadets between the measurements (t20 = -0.962, p > .05). The number of PU1 significantly increased by 10.82% (t20 = -4.191, p < .01). The SU1 significantly increased by 9.34% (t20 = -4.613, p < .01). The 1RM increased on BP by 5.71% (t20 = -5.769. p < .01) and SQ by 7.73% (t = 20, p < .01). The time on 30m sprint decreased by 1.33% (t20 = 7.640, p < .01) and for 5m rope climb decreased by 3.15% (t20 = 6.663, p < .01). Conclusion. The results of this study showed that it is necessary for the naval cadets to follow a WTP during their trips in the sea on a warship to increase their physical condition/fitness and sustain their body composition.